Dynamique des élevages pastoraux et agropastoraux en afrique intertropicale - Alary, Véronique; Duteurtre, Guillaume; Lhoste, Philippe; Richard, Didier; Corniaux, Christian (Uliège Library, 2019)
From 1974 to 2014, intertropical Africa experienced an unprecedented growth in domestic herbivore numbers. Cattle numbers have increased more than twofold, and those of small ruminants by more than threefold. Today, the region accounts for about 20% of the cattle and sheep, 33% of the goats and 81% of the dromedaries raised on the planet. That is to say a livestock population of nearly 900 million head. The book focuses on the dynamics of ruminant and equine livestock in intertropical Africa. It describes the different livestock systems found in arid and sub-humid zones and the available food resources; it discusses the local and global impacts of herbivore farming on the environment. The major socio-economic role of activities around animals and their products, and the growing consumer demand for meat and milk are highlighted. An efficient organization of the livestock-meat chains is reported, while constraints to the establishment of a dairy industry persist. For many families living close to the poverty line, livestock production is a factor in reducing vulnerability. Various services that would enable sustainable development of livestock are described. However, financing methods and monitoring of socio-economic and environmental impacts will have to evolve. The book provides information, key points of understanding and methods for students, development agents and decision-makers faced with the issues of development of these herbivore farms in tropical areas, particularly in Africa, Asia and Brazil.From 1974 to 2014, intertropical Africa has experienced an unprecedented growth in domestic herbivore numbers. Cattle numbers have increased more than twofold, and those of small ruminants by more than threefold. Today, the region accounts for about 20% of the cattle and sheep, 33% of the goats and 81% of the dromedaries raised on the planet. That is to say a livestock population of nearly 900 million head. The book focuses on the dynamics of ruminant and equine livestock in intertropical Africa. It describes the different livestock systems found in arid and sub-humid zones and the available food resources; it discusses the local and global impacts of herbivore farming on the environment. The major socio-economic role of activities around animals and their products, and the growing consumer demand for meat and milk are highlighted. An efficient organization of the livestock-meat chains is reported, while constraints to the establishment of a dairy industry persist. For many families living close to the poverty line, livestock production is a factor in reducing vulnerability. Various services that would enable sustainable development of livestock are described. However, financing methods and monitoring of socio-economic and environmental impacts will have to evolve. The book provides information, key points of understanding and methods for students, development agents and decision-makers faced with the development issues of these herbivore farms in tropical areas, particularly in Africa, Asia and Brazil. / De 1974 à 2014, l'Afrique intertropicale a connu une croissance inédite des effectifs des herbivores domestiques. Les effectifs bovins ont été multipliés par plus de 2, ceux des petits ruminants par plus de 3. Aujourd'hui, la région regroupe environ 20 % des bovins et des ovins, 33 % des caprins et 81 % des dromadaires élevés sur la planète. Soit un cheptel de près de 900 millions de têtes. L'ouvrage est axé sur la dynamique des élevages des ruminants et des équidés en Afrique intertropicale. Il décrit les différents systèmes d'élevage rencontrés en zones aride et subhumide et les ressources alimentaires disponibles ; il aborde les impacts locaux et globaux des élevages des herbivores sur l'environnement. Le rôle socio-économique majeur des activités autour des animaux et de leurs produits, et la demande croissante en viande et lait des consommateurs sont soulignés. Une organisation efficace des filières bétail-viande est rapportée, alors que des contraintes à la mise en place d'une industrie laitière persistent. Pour de nombreuses familles vivant proches du seuil de pauvreté, l'élevage est un facteur de réduction de la vulnérabilité. Divers services qui permettraient un développement durable des élevages sont décrits. Cependant, les modes de financements et les suivis des impacts socio-économiques et environnementaux devront évoluer. L'ouvrage apporte informations, points-clés de compréhension et de méthodes pour les étudiants, les agents de développement et les décideurs confrontés aux questions de développement de ces élevages d'herbivores dans les zones tropicales, notamment en Afrique, en Asie et au Brésil.